Correlation between hindfoot joint three-dimensional kinematics and the changes of the medial arch angle in stage II posterior tibial tendon dysfunction flatfoot. Issue 2 (February 2015) - Zhang, Yi-Jun; Xu, Jian; Wang, Yue; Lin, Xiang-Jin; Ma, Xin
Abstract Background The aim of this study was to explore the correlation between the kinematics of the hindfoot joint and the medial arch angle change in stage II posterior tibial tendon dysfunction flatfoot three-dimensionally under loading. Methods Computed tomography (CT) scans of 12 healthy feet and 12 feet with stage II posterior tibial tendon dysfunction flatfoot were taken both in non- and full-body-weight-bearing condition. The CT images of the hindfoot bones were reconstructed into three-dimensional models with Mimics and Geomagic reverse engineering software. The three-dimensional changes of the hindfoot joint were calculated to determine their correlation to the medial longitudinal arch angle. Findings The medial arch angle change was larger in stage II posterior tibial tendon dysfunction flatfoot compared to that in healthy foot under loading. The rotation and translation of the talocalcaneal joint, the talonavicular joint and the calcanocuboid joint had little influence on the change of the medial arch angle in healthy foot. However, the eversion of the talocalcaneal joint, the proximal translation of the calcaneus relative to the talus and the dorsiflexion of talonavicular joint could increase the medial arch angle in stage II posterior tibial tendon dysfunction flatfoot under loading. Interpretation Joint instability occurred in patients with stage II posterior tibial tendon dysfunction flatfoot under loading. Limitation of over movement of the talocalcaneal joint and the talonavicular joint may help correct the medial longitudinal arch in stage II posterior tibial tendon dysfunction flatfoot.